ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI KLINIK PADA KLINIK 24 JAM XYZ - Malfiany, Rini; Wardana, FX Wisnu (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
Analysis and design of the PHP-based XYZ 24 Hour Clinical Administration System can be used as a solution in handling the patient registration process, recording actions and payments in a clinic. With this PHP-based clinic administration system, it is able to simplify and speed up the performance of officers in providing services effectively and efficiently.In addition, patient administration officers can be given convenience in carrying out initial registration and searching for patient history data previously stored in the visit registration book. In this research, the author discusses how to design a PHP-based clinical administration system at the 24-hour xyz clinic.The system development methodology used is the System Development Life Cycle (SDLC) Waterfall model which includes the stages of system planning, system analysis, system design and system implementation. The system was built using the PHP programming language, the database server uses MySQLThe results achieved in this research are a PHP-based clinical administration system. With the patient administration system at the 24-hour xyz clinic, it is hoped that it can help services including the registration process, recording actions until the patient makes payment, as well as speeding up the search for patient data and maintaining data security.